Analisis Perbedaan Kesejahteraan Antara Anggota dan Non Anggota Badan Usaha Milik Desa Karang Indah Kecamatan Mandastana Kabupaten Barito Kuala - Zarata, Regie; Chandriyanti, Ika (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study was aimed to (1) know the welfare condition between member and non-member of BUMDes Karang Indah (2) understand the strategies that can develop BUMDes to increase the welfare of Karang Indah villagers.The study's Respondents were 76 of the BUMDes member families and 34 of theBUMDes non-member families, their occupations as a farmer, seller, and breeder in Karang Indah Village Mandastana, Barito Kuala. The data were processed by independent sample t-test and SWOT analysis. The study results showed the welfare condition between member and non-member ofBUMDes were different and measured by household income, household expenditure,household saving, education, and employment. These variables showed the non-member ofBUMDes were more in welfare than a member of BUMDes. The results of SWOT analysiswere: (1) cooperating with the bank to lend capital for villagers business; (2) creatingproductive business unit; (3) keeping the stocks of goods; (4) doing socialization aboutBUMDes frequently; (5) fixing the record system of BUMDes income.The village government should fix the management of BUMDes, include strategicplanning, recording system for BUMDes income, and strategies to develop BUMDes. Theyshould do these to avoid the BUMDes existence as a trend and formality, but to increase thevillagers' welfare condition, especially the member of BUMDes.